The new genus Benitotania (Daltoniaceae, Byropsida) from Mt. Kinabalu - Hiroyuki Akiyama; Hiromi Tsubota; Tomio Yamaguchi; Monica Suleiman (Amer Bryological Lichenological Society Inc., 2003)
A new monospeciﬁc genus, Benitotania, is described on the basis of B. elimbata H.Akiyama, T. Yamag, & M. Suleiman, collected in the northern part of Sabah, Malaysia. It appears to be most closely related to Adelothecium and Bryobrothera.